Traceability in the agricultural sector: A review for the period 2017 – 2022 - Hualpa Zúñiga, Andrés Mauricio (2023)
Introduction. Traceability is regarded in business systems as a monitoring and control tool that is centered on measuring and gathering data for efficient resource allocation. The agricultural sector is no stranger to this practice because, like other industrial systems, it integrates control needs at the level of cultivation, supply of inputs, transformation, transportation, and marketing of products. Objective. To identify objects and scopes of monitoring, analysis units, and adoption of traceability trends in the agricultural supply chain, in order to reference the development of recent studies and publications that integrate this control function in this sector. Development. The applied methodology was developed through the search, selection, and analysis of articles in scientific repositories such as Science Direct and AGRIS, to identify trends in agricultural traceability in the years 2017 to 2022. Application and integration trends of traceability systems were recognized in the agricultural sector around different approaches, including digitization and information security, measurement of agricultural productivity and environmental impact mainly within the concept of sustainability. Lines of research are presented in its conclusions, as well as the knowledge gaps for future work. Conclusions. The results of the review in the last six years frame traceability trends mainly in the digital monitoring of cultivation processes, the measurement of productivity, and the environmental impact. The degree of direct intervention in the producer represents the highest proportion in the category of the logistic scope of traceability. Therefore, it is recommended in the future the development of traceability systems that monitor productivity, environmental, and social impact indicators in a convergent manner, as well as the integrated participations of actors in the agricultural sector, including producers, technical advisors, and government entities.